Medial Gastrocnemius Muscle Architecture Is Altered After Exhaustive Stretch-Shortening Cycle Exercise - Kositsky, Adam; Kidgell, Dawson J.; Avela, Janne (Frontiers in Physiology, 2019)
Muscle architecture is an important component of muscle function, and recent studies have shown changes in muscle architecture with fatigue. The stretch-shortening cycle is a natural way to study human locomotion, but little is known about how muscle architecture is affected by this type of exercise. This study investigated potential changes in medial gastrocnemius (MG) muscle architecture after exhaustive stretch-shortening cycle exercise. Male athletes (n = 10) performed maximal voluntary contractions (MVC) and maximal drop jump (DJ) tests before and after an exercise task consisting of 100 maximal DJs followed by successive rebound jumping to 70% of the initial maximal height. The exercise task ceased upon failure to jump to 50% of maximal height or volitional fatigue. Muscle architecture of MG was measured using ultrasonography at rest and during MVC, and performance variables were calculated via a force plate and motion analysis. After SSC exercise, MVC (-13.1%; p = 0.005; dz = 1.30), rebound jump height (-14.8%, p = 0.004; dz = 1.32), and ankle joint stiffness (-26.3%; p = 0.008; dz = 1.30) decreased. Ankle joint range of motion (+20.2%; p = 0.011; dz = 1.09) and MG muscle-tendon unit length (+12.0%; p = 0.037; dz = 0.91) during the braking phase of DJ, the immediate drop-off in impact force (termed peak force reduction) (Δ27.3%; p = 0.033; dz = 0.86), and lactate (+9.5 mmol/L; p < 0.001; dz = 3.58) increased. Fascicle length increased at rest (+4.9%; p = 0.013; dz = 1.16) and during MVC (+6.8%; p = 0.048; dz = 0.85). Pennation angle decreased at rest (-6.5%; p = 0.034, dz = 0.93) and during MVC (-9.8%; p = 0.012; dz = 1.35). No changes in muscle thickness were found at rest (-2.6%; p = 0.066; dz = 0.77) or during MVC (-1.6%; p = 0.204; dz = 0.49). The greater MG muscle-tendon stretch during the braking phase after exercise likely resulted in muscle damage. The lower peak force reduction and ankle joint stiffness, indicative of decreased active stiffness, suggests activation was likely reduced, causing fascicles to shorten less during MVC.